Visibility Strategies: On the Imprudence of the Art on Walls (Altre Modernità, 2021)
This paper examines the common imagery of the inscriptions found on thewalls of some Latin American and European cities. We aim to understand the graffiti andother mural artistic manifestations as an insurgence of the words. In order to reflectcritically on these manifestations, we examine how the visual language of graffiti relatesto visual art and literature. To this end, we follow Aby Warburg's Atlas Mnemosynemethod to address narrative representations as contemporary generational trends.With the help of the theoretical approach of Walter Benjamin's studies of art and politics,we intend to reflect on the aestheticization of revolt through the appropriation of publicspaces. The central point of the paper is to think about walls as places for experimentingwith marginal forms of co-creation that question the strategies of visibility of the urbansemiological regime. As a conclusion, we interrogate the aesthetics of the revolt usingthe notions of territory and contemporary culture. The walls have not only become aspace for political struggle, but also supports for creative urban practices where artmeets the everyday life.
Keywords: Walls; Art; Graffiti; Aesthetics; Revolt